A Comparative Clinical Study on Effect of Samsaptak Choorna and Avipattikar Choorna in Management of Amlapitta - Chavan, Sourabh Bhausaheb (International Research Journal of Ayurveda & Yoga, 2023)
Introduction: In this modern era, we all are undergoing different lifestyle modification related to food and lifestyle. Irregular meal pattern, work in shift duties, irregular sleep timing, craze for fast food, anxiety, and stress-induced hectic unhealthy schedules cause various disorders due to which there has been an extraordinary increase in the disorders related to Annavaha srotas or the gastrointestinal (G.I) system. Burning sensation in chest, sour belching, abdominal discomfort, nausea, vomiting, headache, and constipation are the most common complaints faced in day to-day life. All these symptoms point toward Amlapitta in Ayurveda. If left untreated, it may lead to complications such as ulcerations in the gastrointestinal tract and forward the known medications such as Avipattikar Choorna and Samsaptak Choorna are taken for the study to evaluate their effect and compare their effect.Materials and Methods: 20 patients of Group A were treated with Samsaptak Choorna for 30 days. 20 patients of Group B were treated with Avipattikar Choorna for 30 days’ 20 patients in each group and both groups subjected to Amlapitta treatment: In the first group, doses of Samsaptak Choorna 3 g BID per day in divided doses for period of 30 days and in the second group, doses of Avipattikar Choorna 3 g BID per day in divided doses for period of 30 days. Results: The result of both groups was analyzed statistically and compared and results were interpreted in the term of increase or decrease in the parameter. The statistical analysis reveals that both the groups are showing good result but Group B is slightly more effective result then Group A in Amlapitta. Conclusion: Both the drugs – Samsaptak Choorna and Avipattikar Choorna gave good improvement in both groups.